Tumour necrosis factor and interleukin 10 in blood pressure regulation in spontaneously hypertensive and normotensive rats. (January 2019) - Segiet, Agnieszka; Smykiewicz, Paweł; Kwiatkowski, Piotr; Żera, Tymoteusz
Highlights: We studied the role of TNF and IL-10 in blood pressure control in SH and WKY rats. SH rats had altered cardiovascular reflexes and higher blood pressure than WKY rats. SH rats had greater hemodynamic changes to intrabrain infusions of TNF and IL-10. TNF, TNFR1 and IL-10 were higher and IL-10Ra was lower in the brainstem of SH rats. Proinflammatory shift in cytokines and their receptors is present in hypertension. Abstract: Introduction: A growing body of evidence indicates that brain cytokines are involved in the control of the cardiovascular system. Tumour necrosis factor (TNF) is an archetypal cytokine, which exerts its proinflammatory actions via type 1 receptor (TNFR1). Interleukin 10 (IL-10) plays a critical anti-inflammatory role by binding to its receptor (IL-10Ra). The orchestrated inflammatory response is largely dependent on an intricate balance between proinflammatory and anti-inflammatory cytokines and expression of their receptors. Aim: In the study we evaluated the expression of the cytokines and their receptors in the brains of spontaneously hypertensive (SH) and normotensive Wistar-Kyoto (WKY) rats, and how the cytokines affect arterial blood pressure. Methods: In SH and WKY rats we recorded systolic blood pressure with tail cuff method and measured concentration of TNF, IL-10, TNFR1, and IL-10Ra in the serum, the brainstem, and the hypothalamus; we also measured serum concentrations of copeptin, a surrogate of vasopressin release, angiotensin II and norepinephrine. We immunostained brainstem sections for TNFR1, IL-10Ra, neurons, astrocytes and microglia for confocal imaging. In urethane anaesthetized SH and WKY rats, we invasively recorded blood pressure response to intracerebroventricular (IVC) infusion of TNF or IL-10. We also pharmacologically evaluated baroreflex with phenylephrine and chemoreflex with cyanide in SH and WKY rats. Results: Compared to WKY rats, SH rats had: (1) higher blood pressure; (2) blunted baroreflex and augmented peripheral chemoreflex; (3) greater pressor response to ICV infused TNF and greater hypotensive response to ICV infused IL-10; (4) higher concentration of TNF in the ventral and dorsal aspects of the medulla oblongata; (5) higher expression of TNFR1 in the dorsal medulla; (6) higher concentration of IL-10 in both aspects of the medulla; (7) lower expression of IL-10Ra in the dorsal medulla. Confocal imaging showed co-localization of TNFR1 and IL-10Ra with neurons, astrocytes and microglia in both SH and WKY rats. The concentration of the cytokines and their receptors were significantly higher in the brain than in the serum. There were no significant differences in the concentration of the cytokines and their receptors in the hypothalamic region and in the serum between SH and WKY rats. Serum concentrations of norepinephrine, angiotensin II and copeptin were similar between SH and WKY rats. Conclusions: Taken together, these findings suggest the presence of a potent milieu for effective TNF signalling in the brainstem, which is associated with the hypertensive phenotype and enhanced hemodynamic response to intrabrain administration of the cytokines. In addition, we hypothesize that the increased IL-10 concentration in the brainstem is a compensatory mechanism for the upregulated TNF system.